STUDENTS’ PRESENT CONDITION IN IMPLEMTING ENGLISH FOR HOSPITALITY PROGRAM - Kardijan, Dian; Yundayani, Audi (English Department FBS UNP, 2018)
The main purposes of this study were to (1) find out students’ English communication skill and their perceptions concerning with English proficiencies for employees of hospitality industry field; and (2) identify students’ entry behaviors and their characteristics. The descriptive inquiry was used in identifying students’ present situation drawing through semi-structured interviews and observations. Purposively selected of the respondents, consist of: English teachers and students’ 3rd class who have done field work practice in the hotel. The findings show that students had low English speaking competence caused they seldom practiced and learned to communicate using English in previous studying activities. Furthermore, they had low ambition to learn and practice English communication but they realized the importance of having English speaking competence as employees’ requirement in the hospitality industry field specifically